2020
DOI: 10.3390/su12041432
|View full text |Cite
|
Sign up to set email alerts
|

R&D in Europe: Sector Decomposition of Sources of (in)Efficiency

Abstract: Measuring the efficiency of research and development (R&D) expenditure and innovation policy has gained attention in recent years. This research examines the efficiency of 29 selected European countries for the period ranging from 2007 to 2017 in achieving and obtaining R&D goals. The methodology applied is the data envelopment analysis approach with the inclusion of the missing data approach. The contributions of this research include the following: dynamic analysis is conducted to track changes of (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Results of Conte et al [63] indicate large cross-country differences in terms of measured efficiency. Some authors, such as Skrinjaric [23], confirmed different results in measuring efficiency when choosing different indicators and units. The efficiency results in the individual countries depend on an evaluation of an indicator, input or output, or on a model that was used (input-oriented, output-oriented, or non-oriented).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Results of Conte et al [63] indicate large cross-country differences in terms of measured efficiency. Some authors, such as Skrinjaric [23], confirmed different results in measuring efficiency when choosing different indicators and units. The efficiency results in the individual countries depend on an evaluation of an indicator, input or output, or on a model that was used (input-oriented, output-oriented, or non-oriented).…”
Section: Discussionmentioning
confidence: 97%
“…The analysis results of R&D efficiency in EU countries indicate different trends in the area of R&D in the private and public sectors. There are many other authors ( [23,58,63]) who evaluated R&D in the public sector (higher education and government sectors) and private sector in the European context by using similar input and output indicators as were used in this research. Also, Aristovnik [64] and Hu, Yang, and Chen [28] (as in our study) used expenditure on R&D and the number of full-time researchers as input indicators when assessing the efficiency of R&D by DEA method, and the number of scientific publications indexed in the Science Citation Index as output indicators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These have already achieved better results in the field of innovation, so the concentration of R&D among market leaders is increasing and form barriers to entry for small and medium enterprises [47]. Generally, SMEs have a problem with finding resources in terms of funds, people, knowledge, and other factors needed for innovation and R&D [48][49][50]. Based on the reasons above, it will be necessary to monitor the area of R&D funding, the structure of their resources, as well as to analyze and compare the size of funds used to support these areas from the business enterprise sources, public (government) sources, or foreign sources in the coming years with Agenda 2030.…”
Section: Discussionmentioning
confidence: 99%